“Curhat Yuk! Jangan Pendam Masalahmu”: Layanan Konsultasi Online untuk Membantu Problematika Seputar Masalah Remaja - Yeni Mulati; Eny Purwandari; Nada Mohamed Ibrahim Owida; Rizky Sembada Sapta Putra (Universitas Muhammadiyah Surakarta, 2022)
The very rapid physical, cognitive and social changes in adolescents cause a growth and development crisis that should not be ignored. Adolescence is a time of upheaval and stress. Therefore, adolescents must be accompanied to be able to undergo the process of growth and development. The purpose of this community service is to assist teenagers by providing online vent services, providing solutions to the problems they share, and publishing articles that discuss adolescent problems. The vent service is carried out through the Google Form which is linked on the website www.curhatyuk.net. The target of this activity is youth aged 13-18 years. The answer to the vent was given via email. In a span of 2.5 months, there were 46 teenagers who used online consultations. During this period, 12 articles on popular psychology have been published, written in the language of teenagers. Some of the articles are written based on the problems that users share. In general, this website has a pretty good performance.